KERENTANAN SOSIAL DAN EKONOMI MASYARAKAT DI PERBATASAN KABUPATEN SAMBAS MENGHADAPI PANDEMI COVID-19 - Pabali Musa; Adi Suryadi; Rizqi Ratna Paramitha (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2021)
COVID-19 is categorized as a non-natural disaster that affects the social and economic situation of a region. The COVID-19 pandemic has led to the temporary suspension of activities that have made it difficult to meet economic and social needs. This problem is felt by many parties, one of the affected is people living in the border area. This study is intended to reveal social and economic vulnerabilities in the border areas of Sambas Regency as a result of the COVID-19 pandemic. This research is intended to reveal social and economic vulnerabilities in the border area of Sambas Regency. The method used is a type of qualitative research with the aim of being able to explain intensively and precisely about the research object in question. Data obtained through observation techniques, interviews, and documentation using descriptive analysis. The subject of this research is the Sambas community, especially the workers, both local workers and migrant workers, as well as several related parties.  The results of this study showed that the level of social vulnerability of border communities is not very deep or not severe, due to the still strong socio-cultural and familial ties based on tribal and religious. This base strengthens people's social relations in the face of pandemics. Similarly, vulnerability in the economic field does not look serious because of the good handling and countermeasures system from local governments, as well as the maintained economic backbone of nature-based communities such as agricultures and plantations. COVID-19 dikategorikan sebagai kejadian bencana non alam yang berimbas pada situasi sosial dan ekonomi suatu wilayah. Pandemi COVID-19 berdampak pada pemberhentian aktivitas sementara yang menyebabkan sulitnya pemenuhan kebutuhan ekonomi dan sosial. Permasalahan ini dirasakan oleh banyak pihak, salah satu yang terdampak adalah masyarakat yang tinggal di wilayah perbatasan. Penelitian ini dimaksudkan untuk mengungkapkan kerentanan sosial dan ekonomi di wilayah perbatasan Kabupaten Sambas akibat dari pandemi COVID-19. Metode yang digunakan adalah jenis penelitian kualitatif dengan tujuan agar dapat menjelaskan secara intensif dan tepat tentang objek penelitian yang dimaksud. Data diperoleh melalui teknik observasi, wawancara, dan dokumentasi dengan menggunakan analisis deskriptif. Subjek penelitian ini adalah masyarakat Sambas, khususnya para buruh, baik buruh lokal maupun buruh migran, serta beberapa pihak terkait. Hasil penelitian ini menunjukkan bahwa tingkat kerentanan sosial masyarakat perbatasan tidak terlalu mendalam atau tidak parah, dikarenakan masih kokohnya ikatan sosial budaya serta kekeluargaan yang berbasiskan kesukuan dan keagamaan. Basis ini yang menguatkan relasi sosial masyarakat dalam menghadapi pandemi. Demikian pula kerentanan di bidang ekonomi tidak terlihat serius karena sistem penanganan dan penanggulangan yang cukup baik dari pemerintah setempat, serta masih terjaganya tulang punggung perekonomian masyarakat yang berbasiskan alam seperti pertanian dan perkebunan.